"I guess it looks worse to me, it doesn't look like there's been a problem solved but obviously there is": a qualitative exploration of children's and their parents' views of silver diamine fluoride for the management of carious lesions in children - N. Seifo; H. Cassie; J. R. Radford; N. P. T. Innes (BMC, 2021)
Abstract Background Despite growing evidence to support the use of silver diamine fluoride (SDF) for managing carious lesions, and the increased interest in SDF worldwide, uptake in the UK remains limited. This study explored parents' and children's views and acceptability of SDF for the management of carious lesions in children. Methods Eleven semi-structured face-to-face interviews were conducted with 11 parent-child dyads recruited from patients attending Dundee Dental Hospital and School. Interviews were transcribed verbatim, coded and thematically analysed. Results Previous dental experience varied across all child participants. Of the 11 children, five had undergone general anaesthesia (GA) for multiple primary tooth extractions. Two had received SDF treatment. Child participants expressed concerns about being picked on by their peers, if they had discoloured anterior teeth. Younger children appeared less concerned about the discolouration and child's gender did not appear to influence parents' decision-making, nor the child's preferences regarding the use of SDF. Parents considered SDF to be particularly useful for anxious or uncooperative children but raised concerns about potential bullying at schools due to the unacceptable dental aesthetics when SDF is applied to anterior teeth. They believed they may be judged by others as neglecting their child's oral health due to the black staining. Both parents and children were more accepting of the SDF when applied to less-visible posterior teeth. Parents accepted the use of SDF if such treatment avoided extractions under GA. Conclusion Despite the unfavourable aesthetics of SDF (black staining), parents appreciated SDF treatment, especially for uncooperative or younger children. However, both parents and children shared concerns about bullying at schools as a consequence of the black staining. Raising awareness about SDF was identified as one approach to encourage the uptake of SDF.